Nuclear war : a scenario - Jacobsen, Annie (Torva, 2024)
There is only one scenario other than an asteroid strike that could end the world as we know it in a matter of hours: nuclear war. And it could start in as little as 26 minutes and 40 seconds from now... An edge-of-your-seat non-fiction thriller for readers of American Prometheus by Kai Bird or Midnight in Chernobyl by Adam Higginbotham. The first rule of nuclear war is that there are no rules. Until now, no one outside official circles has known exactly what would happen if a rogue state launched a nuclear missile at the Pentagon. Second by second and minute by minute, these are the real-life protocols that choreograph the end of civilization as we know it. If a single nuclear missile is launched, it provokes two dozen in return. Frantic calls over secure lines work to confirm the worst as armoured helicopters are scrambled outside. Decisions that affect hundreds of millions of lives need to be made within six minutes, based on partial information, in the knowledge that once launched, nothing is capable of halting the destruction. Because the plans for General Nuclear War are among the most classified secrets held by the United States government, this book takes the reader up to the razor's edge of what can legally be known. Based on dozens of new interviews with military and civilian experts who have built the weapons, been privy to the response plans, and taken responsibility for crucial decisions, this is the only account of what a nuclear exchange would look like. Nuclear War is at once a compulsive non-fiction thriller and a powerful argument that we must rid ourselves of these world-ending weapons for ever.